The Meaning of Life of a Single Mother - Firstyana, Rachelia Edelweiss; Wandansari, Yettie (ANIMA Indonesian Psychological Journal, 2010)
There are many challenges that must be faced by a single mother. A single mother is susceptible to stress and frustration. The purpose of this case study was to explore the meaning of life of a single mother. Data collecting method employed was in-depth interview and observation to a working mother who had been a single mother for more than 5 years. The finding of the study is the subject can overcome the challenging situation due to external and internal factors, so that the subject can develop an adaptive coping strategy. The process of life as a single mother finally leads the subject to have a positive meaning of life as a single mother that her life is to give happiness to her child and her family, and that being a single mother leads her to achieve personal maturity. Terdapat banyak tantangan yang harus dihadapi seorang single mother, yang seringkali membuatnya menjadi rentan terhadap stress dan frustasi. Studi kasus ini dilakukan dengan tujuan untuk mengeksplorasi makna hidup pada seorang single mother. Metode pengumpulan data adalah melalui in-depth interview dan observasi pada seorang ibu bekerja yang telah menjalani hidupnya sebagai single mother selama lebih dari 5 tahun. Kesimpulan penelitian ini adalah subjek mampu mengatasi berbagai tantangan karena adanya sejumlah faktor eksternal dan internal, sehingga subjek mampu mengembangkan strategi coping yang adaptif. Proses hidup sebagai seorang single mother akhirnya menghantarkan subjek pada pemaknaan hidup yang positif sebagai single mother, yaitu bahwa hidupnya adalah demi kebahagiaan anak dan keluarga, dan bahwa menjadi seorang single mother telah menempanya untuk mencapai kematangan pribadi.